Pengaruh Brand Image, Word Of Mouth dan Celebrity Endorser Terhadap Purchase Decision Produk Skintific - Salwa Zerina Rangkuti; Satria Mirsya Affandy Nasution (Fisarrearch, 2023)
The purpose of this research is to find out and analyze the effect of brand image on purchasing decisions. To find out and analyze Word Of Mouth on Purchasing Decisions. To find out and analyze Celebrity Endorser on Purchasing Decisions. To find out and analyze the influence of Brand Image, Word Of Mouth and Celebrity Endorser on Purchasing Decisions on the Use of Skintific Products in Medan City. In this study using associative approach to determine the relationship of each variable. The data presented is in the form of quantitative data, namely testing and analyzing data by calculating numbers and then drawing conclusions and testing them. In this study, the objects studied were employees using Skintific Products in Medan City with an unknown population and a sample of 100 people with sampling using the Lemeshow formula. The result of this research is that brand image has a significant effect on purchasing decisions. Word Of Mouth has a significant effect on Purchasing Decisions. Celebrity Endorser has a significant effect on Purchasing Decisions. And Brand Image, Word Of Mouth and Celebrity Endorser have a significant effect on Purchase Decisions on Using Skintific Products in Medan City.